FACTORS ASSOCIATED WITH CARING AMONG ELDERLY WITH END OF LIFE - Eva Riantika Ratna Palupi; Ah. Yusuf (Alta Dharma Publisher, 2019)
The elderly pottentially getting multimorbid disease and chronic disease. Chronic disease through the elderly need an end of life care. The purpose of this study was to found the factors related to the perceptions of end of life care using health belief models. Design of these study was explanatory survey with cross sectional approached. The samples were 118 elderlies in Puskesmas Jatikalen area, Nganjuk Regency. Independent variables were demography (age and gender), sosiopsychological (social class), structural (knowledge), perceived susceptibility, perceived seriousness, perceived benefits, and perceived barriers. Dependent variable was end of life care. Data were collected by interview using questionnaire. Data were analyzed using chi square. Factors related to end of life care in the elderly were age (p value = 0.049), gender (p value = 0.001), social class (p value = 0.002), knowledge (p value = 0.0048), perceived susceptibility (p-value = 0.039), perceived seriousness (p-value = 0.025), perceived benefits (p-value = 0.000), and perceived barriers (p-value = 0.000). The factors related to the end of life care are age, gender, social class, knowledge, perceived susceptibility, perceived seriousness, perceived benefits, and perceived barriers. This study was recommended to apply to the elderly with chronic illnesses, especially at community. Keywords: end of life care, elderly, health belief model